2015
DOI: 10.4103/1793-5482.161191
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive craniectomy in malignant middle cerebral artery infarct: An institutional experience

Abstract: Introduction:Decompressive craniectomy as a surgical treatment for brain edema has been performed for many years and for several different pathophysiologies, including malignant middle cerebral artery (MCA) infarct. The purpose of this article was to share author's experience with decompressive craniectomy in malignant MCA infarct with special emphasis on patients older than 60 years and those operated outside 48 h after onset of stroke.Materials and Methods:Totally, 53 patients who underwent decompressive cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 5 publications
1
19
0
2
Order By: Relevance
“…12 Ross et al had correlated the GCS score with TBI patients and found that 80.5% had GCS score (13-15), 10.5% had GCS score (9)(10)(11)(12) and 9% had GCS score (3-7), 11 which was complementary to the study. Where we concluded 48% had GCS score (13-15), 17% had GCS score (9)(10)(11)(12) and 34% had GCS score (3)(4)(5)(6)(7). Blenow et al disclosed information on FOUR scale score with TBI patients and found 62.86% had score (13-15), 10.67% had score (9)(10)(11)(12) and 26.47% had score (<8) which correlated the study proved that 55% had score (13-16), 14% had (9-12) and 31% had score (<8).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…12 Ross et al had correlated the GCS score with TBI patients and found that 80.5% had GCS score (13-15), 10.5% had GCS score (9)(10)(11)(12) and 9% had GCS score (3-7), 11 which was complementary to the study. Where we concluded 48% had GCS score (13-15), 17% had GCS score (9)(10)(11)(12) and 34% had GCS score (3)(4)(5)(6)(7). Blenow et al disclosed information on FOUR scale score with TBI patients and found 62.86% had score (13-15), 10.67% had score (9)(10)(11)(12) and 26.47% had score (<8) which correlated the study proved that 55% had score (13-16), 14% had (9-12) and 31% had score (<8).…”
Section: Discussionmentioning
confidence: 89%
“…11 Study proved that the current distribution of severe, moderate and mild TBI as 29%, 4% and 67% respectively 11 which was a support to our study, where we have current distribution of severe, moderate and mild as 30%, 2%, 48% respectively. Subjects enrolled in the study were 68% of males and 32% of females which matched the criteria of the study done by Hanish et al 12 who reported 77.1% of males and 22.9% of females. 12 Ross et al had correlated the GCS score with TBI patients and found that 80.5% had GCS score (13-15), 10.5% had GCS score (9)(10)(11)(12) and 9% had GCS score (3-7), 11 which was complementary to the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were supporting several published results, as well as the three main European trials investigating malignant MCA infarcts. The study published by Bansal et al demonstrated mean mRS 3.33 at discharge [2], and the study published by Raffiq MA showed good functional outcome based on mRS in 48.9% of patients at 3 months and in 64.4% of patients at 6 months [11]. Also the pooled analysis of the three European trials showed 43% of cases had favorable functional outcome and 29% mortality rate [9,6,12].…”
Section: Discussionmentioning
confidence: 91%
“…Just removal of the bone flap was proven to reduce ICP by 15%; further reduction, up to 70%, occurs after opening the dura. Elevation of a 12-cm-diameter bone flap will add 86-ml additional volume to the skull [2].…”
Section: Discussionmentioning
confidence: 99%